2014
DOI: 10.7744/cnujas.2014.41.2.125
|View full text |Cite
|
Sign up to set email alerts
|

Variation of glucosinolate contents of 'Sinhongssam' grown under various light sources, periods, and light intensities

Abstract: :The variation of glucosinolates (GSLs) in Chinese cabbage ('Sinhongssam') (Brassica rapa L. spp. pekinensis) cultivated under lights to control plant growth conditions was evaluated at different development stages. Under experimental conditions in plant factory system, plant growth conditions including light, temperature, and nutrients were designed to enhance GSLs. The variation of glucosinolates (GSLs) in Chinese cabbage ('Sinhongssam') (Brassica rapa L. spp. pekinensis) cultivated under lights to control p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
1
1
0
1
Order By: Relevance
“…Overall, glucosinolate content linearly increased until the last day of this study (28 days). This result is consistent with a previous study where glucosinolate content increased in Chinese cabbages cultivated in a plant factory under various lighting conditions until the end of the experimental period (56 days of seeding), regardless of light source, period and light intensity . However, contrary studies reported that glucosinolate content in Brassica species decreased during growth stage .…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Overall, glucosinolate content linearly increased until the last day of this study (28 days). This result is consistent with a previous study where glucosinolate content increased in Chinese cabbages cultivated in a plant factory under various lighting conditions until the end of the experimental period (56 days of seeding), regardless of light source, period and light intensity . However, contrary studies reported that glucosinolate content in Brassica species decreased during growth stage .…”
Section: Resultssupporting
confidence: 93%
“…Among these functional components, glucosinolate is unique to cruciferous vegetables and has become a target for developing functional food . The amount of glucosinolate in cruciferous vegetables is known to depend on genetic features and growing conditions such as pH, temperature, humidity and soil nutrients . Until now, most studies on glucosinolates have mainly focused on physiological or metabolic characterization, while studies about the relationship with growth conditions were relatively fewer.…”
Section: Introductionmentioning
confidence: 99%
“…특히 건조한 환경에서 토양의 수분 보유 능력을 증가시키고 작물이 사용할 수 있는 물의 공급을 조절 함으로써 생육 및 활착을 개선하는 것으로 알려져 있다 [15]. SAP는 국화(Chrysanthemum) 재배에서 처리량에 따라 관 수량이 감소하였고 [4], 배추(Brassica rapa L.)에서는 토양 보 수력의 중대로 생육 및 양분 흡수량이 증대되었으며 [16], SAP 를 상토의 혼용재료로 사용하는 경우 혼합 상토의 보수성이 개선되었다 [17]…”
unclassified
“…따라서 간척지에서는 염 피해에 강한 내염성 작물을 선 발하여 재배하는 것이 유리하며, 간척지에서 재배하고자 하는 작물의 염 농도에 대한 생육을 정량적으로 파악할 필요가 있다. 배추과(Brassicaceae) 작물은 아시아 국가에서 대량으로 재배하며 식단에 중요한 역할을 하는 채소이다 (Lee et al, 2014a(Lee et al, , 2014b. 그 중, 배추(Brassica rapa L. ssp.…”
unclassified
“…그러나 배추과 작물의 글루코시놀레이트 함량은 재배 작형이나 기후조건, 작물의 영양상 태, 품종 등에 따라 많은 차이를 보인다 (Shim et al, 2018). 기존에는 광질 또는 광주기, 광량 등을 변화시켜 배추의 글루코시놀 레이트 함량 변화를 추적하거나 (Lee et al, 2014b;Moon et al, 2015), 배추에 생석회를 시비하여 총 글루코시놀레이트 함량 을 증대시킨 사례 등이 보고되었다 (Kim et al, 2015). 그러나 간척지에서 염 농도에 따른 글루코시놀레이트 함량 분석은 배추 과 작물인 순무에서만 행해졌으며 (Jo et al, 2018), 배추에 대해서는 염 농도에 따른 글루코시놀레이트 함량 변화가 가공처리 단계에서만 연구되었다 (Hwang, 2010;Kim et al, 2010b 로 제염이 진전된 상황이다 (Sohn et al, 2010).…”
unclassified